Triazolobithiophene Light Absorbing Self-Assembled Monolayers: Synthesis and Mass Spectrometry Applications - Kenfack, Ghislain Tsague (Molecules, 2011)
The synthesis of five light absorbing triazolobithiophenic thiols, which were utilized for producing self-assembled monolayers (SAMs) on gold surfaces, is presented. The monolayer formation was monitored by cyclic voltammetry, indicating excellent surface coverage. The new triazolobithiophenic compounds exhibited an absorption maximum around 340 nm, which is close to the emission wavelength of a standard nitrogen laser. Consequently these compounds could be used to aid ionization in laser desorption mass spectrometry (MS).